Efecto de la edad de destete sobre el crecimiento en terneras de reemplazo en ganadería de leche. - Solís Castro, Emely Elizabeth (2022)
The present work was based on the review and analysis of the effect of weaning age on growth in replacement calves in dairy farming. Being weaning a stage in which the calf is subjected to stress due to age change, with the objective of identifying the effect of age at weaning on growth in replacement calves in dairy farming, the methodology was based on information obtained from the dspace of the universities, bibliographies of academic Google, other bibliographic consultation spaces, indexed journals and scientific articles. Likewise, concluding, it is very important to take care that the calf drank colostrum as soon as possible after birth. The feeding of replacement calves should be given special attention since they are going to be the future of the cattle herd. Likewise, it is important to identify and keep records. The weaning and growth stage is very important because it provides the necessary conditions for the calf to grow and acquire optimal body function to start its reproductive stage.